UJI BEDA KONTRIBUSI PAJAK DAN RETRIBUSI DAERAH ANTARA SAAT PPKM DIPERKETAT DAN SETELAH PPKM DIPERLONGGAR - Hana Nur Sahari; Rudy Badrudin (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to determine the impact of the Covid-19 pandemic on Regional Tax and Regional Levy revenues. More precisely, to test and analyze whether there is a difference in contribution between Regional Tax and Regional Levy between when PPKM rules are tightened and after PPKM rules is relaxed. The sample selection in this study used the judgment sampling method. The data used as an analysis tool is data on the realization of regional tax revenues and regional levies in Surakarta City from 2020 to 2022 obtained from the BPKAD Surakarta City. The results of this study show that there is a difference in regional tax contributions in Surakarta City between when PPKM is tightened and after PPKM is relaxed, and there is no difference in regional levy contributions in Surakarta City between when PPKM is tightened and after PPKM is relaxed.